Optimizing the Potential of Halal Media and Entertainment in Indonesia: Analysis of Opportunities, Challenges, and Strategic Steps - Rossy Endah Permata Sari; Sarah Syukri; Wahyuddin Luthfi Abdullah; Hamdi, Baitul (Jurnal Ilmiah Ekonomi Islam, 2025)
This study aims to identify the opportunities and challenges and formulate strategies for developing halal media and entertainment in Indonesia. This research is a library research using a qualitative approach. The study was conducted by reading, reviewing, and analyzing various existing literatures, such as books, journals, news, and research findings. The study results indicate that Indonesia's main opportunities for halal media and entertainment include a significant market potential, global demand for Islamic media content, and the positive influence of social media and digital technology development. However, the industry also faces significant challenges, such as limited definitions and halal standardization, the perception that it limits creativity, the dominance of non-halal content, a lack of innovation, and challenges in filtering and monitoring digital content. To overcome these challenges and optimize potential, the proposed strategies include strengthening the regulatory framework and government policies, improving the quality and diversity of content, developing competent human resources, building an integrated industrial ecosystem, and educating and promoting halal media literacy to the public. Implementing these strategies is expected to drive the industry's growth, contribute to the national economy, and position Indonesia as a global Islamic economy hub.